THE DEVELOPMENT OF FINANCIAL TECHNOLOGY (FINTECH) AND ITS IMPACT ON THE CONVENTIONAL BANKING SYSTEM - Loso Judijanto; Andueriganta Fadhlihi; Fenni Yufantria (Adisam Publisher, 2026)
The development of financial technology (Fintech) has brought about important changes in the traditional banking system. Fintech is introducing innovative solutions that make financial services more efficient, faster and accessible to the masses. Technologies such as blockchain, artificial intelligence (AI), and big data analytics enable financial services that are more personalised and responsive to user needs. However, these advancements also challenge conventional banks to adapt quickly, develop digital services, and invest in technological innovation. Increased competition and the need to update regulations and data security are the main challenges that traditional banks must face in this digital era.